+0  
 
+1
140
1
avatar+211 

Factor the follwing:

 

 5ax^2 + x^3 - 5a - x

 

a^2 - b^2 + 12b - 36 

 

3x^3 - x^2y +6x^2y - 2xy^2 + 3xy^2 - y^3


 

 Aug 29, 2018
 #1
avatar+971 
+3

1. 

 

\(5ax^2 + x^3 - 5a - x\\ =(5ax^2-5a)+(x^3-x)\\ =5a(x^2-1)+x(x^2-1)\\ =(x^2-1)(5a+x)\\ =(x-1)(x+1)(5a+x)\\\)

2. 


\(a^2 - b^2 + 12b - 36\\ =a^2 - (b^2 - 12b + 36)\\ =a^2 - (b - 6)^2\\ =[a - (b - 6)][a + (b - 6)]\\ =(a - b + 6)(a + b - 6)\)

 

3.

 

\(3x^3 - x^2y + 6x^2y - 2xy^2 + 3xy^2 - y^3\\ =x^2(3x - y) + 2xy(3x - y) + y^2(3x-y)\\ =(3x - y)(x^2 + 2xy + y^2)\\ =(3x - y)(x + y)^2\)

 

I hope this helped,

 

Gavin

 Aug 29, 2018

6 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.